AB0385 Anti-chromatin antibodies: a useful marker for early activity. (23rd January 2014) - Arbelaez, A.; Mora, C.; Romero-Sánchez, C.; Valencia-Toro, P.; Londono, J.; Muñoz, D.; Cortes, A.; Jaimes, D.; Valle-Oñate, R.
Abstract : Background: The anti-chromatin antibody is frequently is elevated in patients with active SLE and its titer correlates with activity. Objectives: The objective of this study is to determine the diagnostic value of anti-chromatin antibodies in the assessment of clinically active SLE. Methods: A cross-sectional study with 74 patients (110 samples) diagnosed with SLE. Disease activity was evaluated by Safety of Estrogens in SLE National Assessment— SLE Activity Index (SELENA-SLEDAI) and the British Isles Lupus Activity Group 2004 (BILAG 2004) index. Serological titers of anti-dsDNA high avidity, anti-chromatin and anti-C1q antibodies were measured by enzyme-linked immunosorbent assay (ELISA) using commercially available kits INOVA Diagnostics, Inc. Complement levels by nephelometric test Values in this study were expressed as mean ± standard deviation (SD). The chi-squared test was used for the categorical variables as needed. The Wilcoxon Rank-Sum Test was used for comparison of SLEDAI score indices. Correlation among the levels of complements, anti-dsDNA, anti-chromatin, anti-C1q antibodies and disease activity scores was made by the nonparametric Spearman's rank correlation test (correlation coefficient ρ [rho]). Values of p< 0.05 were considered to be of statistical significance. STATA SE-11, 1 (STATA Corp®) was used. Results: The mean SLEDAI score was 3, 36 ± 3, 19 (0-14). 49, 9% (n=54) of patients had a SLEDAI score of ≥ 4. Activity by BILAG A/B: Renal 9% (n=10), mucocutaneous 8, 18 (n=9), musculoskeletal 6, 5% (n=7), neuropsychiatric 1, 8% (n=2), hematological 1, 8% (n=2), cardiorespiratory and constitucional 0, 9% (n=1). 60% of patients had activity by SLEDAI or BILAG. Biomarkers: Anti-chromatin antibodies 64, 08 ± 74, 3 (1-251), anti-dsDNA 54, 99 ± 77, 63 (12-543), anti-C1q antibodies 14, 66 ± 23, 09 (2-153), C3 97, 81± 30, 5 (26-152) and C4 16, 53 ± 8, 99 (2-42). The prevalence of positive anti-chromatin, anti-dsDNA and anti-C1q antibodies in the recruited patients was 51%, 45%, and 16% respectively. Anti-chromatin antibodies and anti dsDNA antibodies were found to be positive in 70% and 72% active-SLE patients by SLEDAI ≥ 4 (p<0, 0001). Anti-chromatinantibodies were found to be positive in 15, 4% SLE patients lacking anti-dsDNA antibody, 53% without activity for SLEDAI o BILAG at the moment of the study. The Wilcoxon Rank-Sum Test showed an excellent correlation between anti-chromatin antibodies and SLEDAI score ≥ 4 (p< 0, 0001). Spearman's rank correlation test (ρ) among the levels of anti-chromatina and anti-dsDNA with disease activity scores was 0, 38 (p<0, 001) and 0, 41 (p<0, 001) respectively. Conclusions: Anti-chromatincould precede the development of lupus flares and thus has a value in predicting lupus flares and preempting treatment. References: Translational Research 2012;159:326–342. Arthritis Research & Therapy 2009, 11:R154. Ann Rheum Dis 2007;66:693–696. Disclosure of Interest: None Declared